GAMBAR SEBAGAI ALAT KOMUNIKASI VISUAL - H. Istanto, Freddy (Nirmana, 2000)
The language of drawing is necessarily required in modern world nowadays especially during information-communication era%2C the role of drawing is expanding. Drawing is not only important for designer%2C but also crucial for the experts of engineering%2C education%2C bussiness%2C social%2C politics and industry. This article will impart the details from the history drawing was discovered to its function as a means of communication in modern era. Abstract in Bahasa Indonesia : Bahasa gambar sangat dibutuhkan dalam dunia modern saat ini%2C dalam era komunikasi -informasi ini peran gambar semakin besar saja. Gambar tidak saja penting bagi desainer%2C tetapi juga penting bagi ahli-ahli teknik%2C pendidikan%2C bisnis%2C sosial%2C politik dan industri. Tulisan ini akan merinci dari sejarah ditemukannya gambar sampai fungsi gambar sebagai alat komunikasi dalam dunia modern saat ini. drawing%2C communication%2C visual communication